Urgensi Layanan Bimbingan Konseling Pada Pendidikan Anak Usia Dini Kota Pangkalpinang - Paramitha, Siska Dwi (Department of Islamic Guidance and Counseling, 2023)
Abstract Guidance and counseling services have become a necessity and familiar in the world of education. At this time guidance and counseling services in schools were only at the junior high school (SMP) and high school (SMA) levels, but not at the most important levels such as early childhood education (PAUD) and elementary school (SD). Guidance and counseling services themselves cannot be separated and all groups ranging from children to the elderly must be able to get these services, starting from the early childhood education level to tertiary institutions also need these services so that students can achieve psychological well-being.The method used in this research approach is descriptive qualitative with the aim of being able to see the urgency of guidance and counseling services in early childhood education in the city of Pangkalpinang. From the results obtained, it turns out that of the eight early childhood education schools in Pangkalpinang city, there has not been a single guidance and counseling service specifically provided by the institution, this has an impact on not handling properly and appropriately the problems experienced by students and other parties. parents or guardians of students and this will certainly endanger the development of students for the next period. KEYWORDS: Guidance and counseling services, early childhood, PAUD Abstrak layanan BK sudah menjadi kebutuhan dan akrab di dunia pendidikan. Pada masa ini layanan bimbingan dan konseling di sekolah hanya berada di tingkat sekolah menengah pertama dan sekolah menengah atas, namun tidak di tingkat paling utama seperti pendidikan anak usia dini dan sekolah dasar. Layanan bimbingan dan konseling sendiri tidak bisa dipisahkan dan semua kalangan mulai dari anak-anak hingga lanjut usia harus bisa mendapatkan layanan ini, mulai dari tingkat PAUD hingga perguruan tinggi juga membutuhkan layanan ini agar peserta didik dapat mencapai kesejahteraan dari sisi psikologis. Metode yang digunakan dalam pendekatan penelitian ini adalah deskriptif kualitatif dengan tujuan agar dapat melihat urgensi dari layanan bimbingan dan konseling pada pendidikan anak usia dini di kota Pangkalpinang. Dari hasil yang didapatkan ternyata dari kedelapan PAUD di kota Pangkalpinang, belum ada satu pun layanan BK secara khusus diberikan oleh pihak lembaga, hal ini berdampak pada tidak tertanganinya dengan baik dan tepat masalah-masalah yang dialami. KATA KUNCI: Layanan bimbingn dan konseling, Anak Usia Dini, PAUD